Oxidants, Antioxidants, and Impact of the Oxidative Status in Male Reproduction - Henkel, Ralf; Samanta, Luna; Agarwal, Ashok (Physician) (Academic Press, an imprint of Elsevier, 2018)
"Oxidants, Antioxidants and Impact of the Oxidative Status in Male Reproduction is an essential reference for fertility practitioners and research and laboratory professionals interested in learning about the role of reactive oxygen species in sperm physiology and pathology. The book focuses on unravelling the pathophysiology of oxidative stress mediated male infertility, recruiting top researchers and clinicians to contribute chapters. This collection of expertise delves into the physico-chemical aspects of oxidative stress, including a new focus on reductive stress. Furthermore, the inclusion of clinical techniques to determine oxidative stress and the OMICS of reductive oxidative stress are also included. This is a must-have reference in the area of oxidative stress and male reproductive function. Offers comprehensive information on oxidative stress and its role in male reproduction, including new therapeutic approachesDeals with current approaches to oxidative stress using OMICS platform<Designed for fertility practitioners, reproductive researchers, and laboratory professionals interested in learning about the role of reactive oxygen species in sperm physiology and pathology"--